2018
DOI: 10.26905/jmdk.v6i2.2277
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Corporate Social Responsibility dan Komisaris Independen terhadap Agresivitas Pajak

Abstract: AbstrackThis study aims to determine the effect of the corporate sosial responsibility and independent commissioners on tax aggressiveness. This study are conducted on 130 firm-years manufacturing firms listed in the Indonesian Stock Exchange during period of 2012 to 2016, selected based on purposive sampling method. Tax aggressiveness is proxy by ETR. Corporate social responsibility activities measured based on disclosures referring to Gobal Reporting Initiative (GRI) guideline. Independent commissioner is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
1
5
0
7
Order By: Relevance
“…And corporate social responsibility also affects tax aggressiveness. The results of this study are also in line with the results of research by Simorangkir et al (2018), which concluded that corporate social responsibility and independent commissioners negatively affect tax aggressiveness. The company's success can be supported by good corporate governance and social responsibility implemented by the company.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…And corporate social responsibility also affects tax aggressiveness. The results of this study are also in line with the results of research by Simorangkir et al (2018), which concluded that corporate social responsibility and independent commissioners negatively affect tax aggressiveness. The company's success can be supported by good corporate governance and social responsibility implemented by the company.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, Simorangkir et al (2018) show that corporate social responsibility and independent commissioners harm tax aggressiveness. The Audit Committee, Independent Commissioner, and Corporate Social Responsibility together or simultaneously significantly influence Tax Aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With stronger supervision, management will more carefully make decision and transparently operate the company, thus tax avoidance may be minimized for the company to maintain its survival. The research conducted by Simorangkir et al, (2018) states that it is important for independent commissioner to monitor corporate behaviors or attitudes and decisions in consideration of the needs of the society and in compliance with prevailing regulations where company operates its business. Therefore, independent commissioner must be able to monitor management's attitudes, behaviors, decisions and acts so that they will not perform any act which may threaten company's legitimacy, such as tax aggressiveness.…”
Section: Independent Commissioner Moderates Corporate Social Responsimentioning
confidence: 99%